2021
DOI: 10.1093/cz/zoab010
|View full text |Cite
|
Sign up to set email alerts
|

Tri-axial accelerometry shows differences in energy expenditure and parental effort throughout the breeding season in long-lived raptors

Abstract: Cutting-edge technologies are extremely useful to develop new workflows in studying ecological data, particularly to understand animal behaviour and movement trajectories at the individual level. Although parental care is a well-studied phenomenon, most studies have been focused on direct observational or video recording data, as well as experimental manipulation. Therefore, what happens out of our sight still remains unknown. Using high-frequency GPS/GSM dataloggers and tri-axial accelerometers we monitored 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 69 publications
1
22
0
Order By: Relevance
“…In this way, the nest may indicate parental quality, experience or genetic quality, and therefore females could benefit from mating with good nest-building males 13 . Previous studies describing bi-parental care in Bonelli’s Eagles have shown a sex-biased specialization in parental duties 48 , 79 . Females invested significantly more effort than males in gathering nest-material during the incubation and offspring attendance period 48 .…”
Section: Discussionmentioning
confidence: 85%
“…In this way, the nest may indicate parental quality, experience or genetic quality, and therefore females could benefit from mating with good nest-building males 13 . Previous studies describing bi-parental care in Bonelli’s Eagles have shown a sex-biased specialization in parental duties 48 , 79 . Females invested significantly more effort than males in gathering nest-material during the incubation and offspring attendance period 48 .…”
Section: Discussionmentioning
confidence: 85%
“…Thus, if male investment in nest construction is a consistent trait of any particular male, it is likely that females will use male nest-building effort to assess male parental quality and that the amount of branches and sticks that males deliver to the nest would become a sexually selected trait 20,33 . Previous studies describing biparental care in Bonelli's Eagles have shown a sex-biased specialization in parental duties 51,91 . Females invested signi cantly more effort than males in gathering nest-material during the breeding season 51 .…”
Section: Discussionmentioning
confidence: 99%
“…The weight of the transmitters was 48 and 50 g, respectively, and represented 1.66 to 2.86% (average = 2.25%, SD = 0.38%) of the body mass of eagles, below the 3% threshold established to avoid negative effects on behavior (Kenward, 2001;García et al 2021). The duty cycle of the transmitters was programmed to record a GPS location at five-minute intervals (López-López et al, 2021), from 1 h before sunrise to 1 h after sunset, year-round. Transmitters' data was retrieved, stored and managed by means of the Movebank online repository (http://www.movebank.org/).…”
Section: Trackingmentioning
confidence: 99%